Konsep Manajemen Mutu Pendidikan Pada Lembaga Pendidikan Tinggi Islam - Tarmizi Tahir; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Journal on Education, 2024)
This exploration plans to portray the idea of instructive quality administration in Islamic instructive organizations. This study utilized subjective examination strategies. The information involved by the creator in this examination is a significant information source and is like the conversation being considered. The information assortment technique in this exploration is Library Exploration. The exploration results show that quality administration is an approach to dealing with an association that is extensive and coordinated which is aimed at reliably addressing client needs and accomplishing persistent improvement in each part of hierarchical exercises. Aside from that, quality administration is likewise an interaction technique to further develop execution and increment the nature of work by underlining process ensures so the items delivered can fulfill quality guidelines. The idea of value the board in instructive establishments is an approach to dealing with all instructive assets to create instructive administrations that meet or even surpass client needs. During the time spent carrying out training quality administration, essential systems are required so the ideal objectives can be accomplished as per the quality focuses on that have been set.